2023
DOI: 10.1038/s41598-023-41502-w
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of Mentha piperata-derived biogenic zinc oxide nanoparticles against UTI-resistant pathogens

Nisar Ahmad,
Shujat Ali,
Muhammad Abbas
et al.

Abstract: Misuse of antibiotics leads to the worldwide spread of antibiotic resistance, which motivates scientists to create new antibiotics. The recurring UTI due to antibiotics-resistant microorganism’s challenges scientists globally. The biogenic nanoparticles have the potential to meet the escalating requirements of novel antimicrobial agents. The green synthesis of nanoparticles (NPs) gained more attention due to their reliable applications against resistant microbes. The current study evaluates the biogenic ZnO NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…This result aligns closely with values of approximately 450 nm reported in previous studies. 60,61 Typically, AgNPs exhibit a unique SPR ranging from 400 to 480 nm wavelengths, 62 consistent with the findings of this research. Importantly, the SPR peak at 449 nm remained unchanged even after four months of incubation, indicating the stability and reliability of the green-synthesized RFL-AgNPs.…”
Section: Discussionsupporting
confidence: 84%
“…This result aligns closely with values of approximately 450 nm reported in previous studies. 60,61 Typically, AgNPs exhibit a unique SPR ranging from 400 to 480 nm wavelengths, 62 consistent with the findings of this research. Importantly, the SPR peak at 449 nm remained unchanged even after four months of incubation, indicating the stability and reliability of the green-synthesized RFL-AgNPs.…”
Section: Discussionsupporting
confidence: 84%
“…Ahmed et al , reported similar findings that the obtained biogenic ZnONPs synthesized by using Mentha piperata extract exhibited high purity. 70…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 1517–1528 cm −1 were indicative of the C-H bending vibrations in aromatic rings, characteristic of the presence of aromatic compounds. The peak at 1402 cm −1 , typical for amine or amide, represented the presence of the N-H bending of the organic compound, indicating the presence of a nitrogen-containing compound [ 47 ]. The bonds in the range of 1129–1140 cm −1 were assigned to C–O–H in phenolic compounds [ 33 ].…”
Section: Resultsmentioning
confidence: 99%